1992
DOI: 10.2307/2336782
|View full text |Cite
|
Sign up to set email alerts
|

Nonparametric Tests of the Markov Model for Survival Data

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Biometrika Trust is collaborating with JSTOR to digitize, preserve and extend access to Biometrika. SUMMARYJones & Crowley (1989) introduced a general class of nonparametric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 5 publications
0
37
0
Order By: Relevance
“…However, empirical evidence has shown that truncation may reveal useful information on the lifetime of interest (Tsai 1990;Jones and Crowley 1992;Chen et al 1996;Martin and Betensky 2005;Emura and Wang 2010;Rodríguez Girondo and de Uña-Álvarez 2012). In this article, we explicitly include the truncation variable, along with other covariates, in the proposed semiparametric AFT regression model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, empirical evidence has shown that truncation may reveal useful information on the lifetime of interest (Tsai 1990;Jones and Crowley 1992;Chen et al 1996;Martin and Betensky 2005;Emura and Wang 2010;Rodríguez Girondo and de Uña-Álvarez 2012). In this article, we explicitly include the truncation variable, along with other covariates, in the proposed semiparametric AFT regression model.…”
Section: Discussionmentioning
confidence: 99%
“…We implement computing routines for the proposed method in R depend.truncation package which is freely available through the Comprehensive R Archive Network (CRAN) http://cran.rproject.org/". Jones and Crowley (1992) also included the truncation variable as a covariate based on their models. However, their paper focused only on testing the assumption of quasiindependence without estimating the models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals are right censored if they were alive as of 2006. We tested the independence of the left-truncation time and age at death using Jones and Crowley's (1992) approach based on the Cox model. There was a significant association (P¡0.0001).…”
Section: Examplementioning
confidence: 99%
“…A test based on the productmoment correlation has been proposed by Chen et al (1996). Alternatively, Jones and Crowley (1992) proposed the use of Cox's model for testing the association. In particular, they model the conditional distribution of time-to-event given truncation time using Cox's model for left-truncated data (Andersen et al, 1997).…”
Section: Introductionmentioning
confidence: 99%